2005
DOI: 10.1029/2004je002373
|View full text |Cite
|
Sign up to set email alerts
|

Crustal extension in the Ceraunius Fossae, Northern Tharsis Region, Mars

Abstract: [1] We investigated the Ceraunius Fossae area, Northern Tharsis, in order to obtain quantitative information on the tectonic extension affecting this area. Tectonic structures of the Ceraunius Fossae area have been previously described using Viking images and interpreted as extensional structures. Laser altimetry data (MOLA) can be used to quantitatively investigate these structures with a better resolution. We developed a method to obtain E-W oriented profiles (perpendicular to the main tectonic structures) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…From the pioneer works of Carr [1974], Wise et al [1979], and Melosh [1980], tectonic structures on the Tharsis dome have been extensively studied. Some highlights of this intense scrutiny are the identification of several episodes of tectonism [ Plescia and Saunders , 1982], the publishing of Tharsis paleotectonic maps [ Scott and Dohm , 1990], the mapping of stress fields [ Tanaka et al , 1991], the hypothesis of nonhydrostatical stresses to account for the contractive deformation [ Watters , 1993], countered by Banerdt and Golombek [2000], who attributed the deformation to flexure alone, the tentative reconstruction of tectonic stages by Anderson et al [2001], and the in‐depth regional studies of Hauber and Kronberg [2001] at Tempe Fossae, Cailleau et al [2003] at Alba Patera, Wilkins and Schultz [2003] at Valles Marineris, or Borraccini et al [2005] at Ceraunius Fossae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the pioneer works of Carr [1974], Wise et al [1979], and Melosh [1980], tectonic structures on the Tharsis dome have been extensively studied. Some highlights of this intense scrutiny are the identification of several episodes of tectonism [ Plescia and Saunders , 1982], the publishing of Tharsis paleotectonic maps [ Scott and Dohm , 1990], the mapping of stress fields [ Tanaka et al , 1991], the hypothesis of nonhydrostatical stresses to account for the contractive deformation [ Watters , 1993], countered by Banerdt and Golombek [2000], who attributed the deformation to flexure alone, the tentative reconstruction of tectonic stages by Anderson et al [2001], and the in‐depth regional studies of Hauber and Kronberg [2001] at Tempe Fossae, Cailleau et al [2003] at Alba Patera, Wilkins and Schultz [2003] at Valles Marineris, or Borraccini et al [2005] at Ceraunius Fossae.…”
Section: Introductionmentioning
confidence: 99%
“…This tectonic transport would explain a number of important transcurrent and thrusting structures, including some rhomb‐horst alignments indicative of local transpressional tectonics. On the other side, Borraccini et al [2005] concluded that a significant horizontal crustal motion was needed to explain Ceraunius Fossae, a set of graben near the Tharsis center. The contrast between “load” and “thrust” hypotheses has been increasing as the investigations on Tharsis’ structure accumulated.…”
Section: Introductionmentioning
confidence: 99%
“…Scott and Tanaka (1986) map the east wing of the CFF as extending beyond the northern and eastern limits of the radar-bright feature. However, the revised mapping by Tanaka (1990) redesignates this region as late-Hesperian and shrinks the NE boundaries of the CFF into much better agreement with the boundaries of the radar feature (see also Borraccini et al, 2005Borraccini et al, , 2006. The map of Scott and Tanaka (1986) also shows the CFF extending below 20°N latitude into the region east of the Jovis Tholus shield (7-V).…”
Section: West-slope Flows and Minor Shields; Ceraunius Fossaementioning
confidence: 93%
“…The eponymous Ceraunius Fossae (or CF) comprises three lobes of fractured terra of late-Noachian to early-Hesperian age that are characterized by dense clusterings of N/S-aligned graben (Scott and Tanaka, 1986;Tanaka, 1990;Borraccini et al, 2005Borraccini et al, , 2006. The CF rises above, and is embayed, by the younger CFF flows.…”
Section: West-slope Flows and Minor Shields; Ceraunius Fossaementioning
confidence: 99%
“…The graben zone passes through the Tharsis rise diagonally, cutting through Alba Patera, Ceraunius Fossae, the Local subduction and fi nal unifi cation of a global plate-tectonic network | RESEARCH Tharsis Montes, and Claritas Fossae (Figs. 2, 3, and 4; e.g., Scott and Tanaka, 1986;Borraccini et al, 2005;Hauber and Kronberg, 2005;Carr, 2006;Dohm et al, 2009b). Individual grabens are expressed by closely spaced topographic depressions either bounded by normal faults or underlain by dikes (e.g., Anderson et al, 2001;Wyrick et al, 2004;Schultz et al, 2006Schultz et al, , 2008Polit et al, 2009;Wilson and Head, 2002;Scott et al, 2002;Wyrick and Smart, 2009).…”
Section: Main Tharsis Graben Zonementioning
confidence: 99%